2-6j+8j=-2j-10

Simple and best practice solution for 2-6j+8j=-2j-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-6j+8j=-2j-10 equation:


Simplifying
2 + -6j + 8j = -2j + -10

Combine like terms: -6j + 8j = 2j
2 + 2j = -2j + -10

Reorder the terms:
2 + 2j = -10 + -2j

Solving
2 + 2j = -10 + -2j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '2j' to each side of the equation.
2 + 2j + 2j = -10 + -2j + 2j

Combine like terms: 2j + 2j = 4j
2 + 4j = -10 + -2j + 2j

Combine like terms: -2j + 2j = 0
2 + 4j = -10 + 0
2 + 4j = -10

Add '-2' to each side of the equation.
2 + -2 + 4j = -10 + -2

Combine like terms: 2 + -2 = 0
0 + 4j = -10 + -2
4j = -10 + -2

Combine like terms: -10 + -2 = -12
4j = -12

Divide each side by '4'.
j = -3

Simplifying
j = -3

See similar equations:

| 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 | | 3y-6y^2=0 | | 25=-7(x+5)+5x | | 5x+8y=6e | | 3x+5=350 | | 8=-4x+x+8 | | ln*(x+3)+ln*9=1 | | 8(x+9)=80 | | (-34)+50+50= | | 85-3x=4 | | -5n=13-13m | | 6x-2y=4x+6y | | y=2x^2-7x-30 | | 8x^2=4x+14 | | 6a+12=6a-12 | | p=8p+p | | -2y=14x-50 | | 12x+8-3x=-1 | | b-8+2b=24 | | 5x-14=-24 | | 13x-7=4x+29 | | 14=-5n-2n |

Equations solver categories